Fuzzy approximate entropy analysis of resting state fMRI signal complexity across the adult life span. Issue 11 (November 2015) - Sokunbi, Moses O.; Cameron, George G.; Ahearn, Trevor S.; Murray, Alison D.; Staff, Roger T.
Highlights: The method for fMRI signal complexity analysis using fApEn is presented. fApEn significantly associated with age. The fApEn-ageing effect in white matter and gray matter are both significant. These results support the Goldberger/Lipsitz model for complexity and robustness. fApEn is a potentially reliable method for the complexity analysis of fMRI data. Abstract: In this study, we present a method for measuring functional magnetic resonance imaging (fMRI) signal complexity using fuzzy approximate entropy (fApEn) and compare it with the established sample entropy (SampEn). Here we use resting state fMRI dataset of 86 healthy adults (41 males) with age ranging from 19 to 85 years. We expect the complexity of the resting state fMRI signals measured to be consistent with the Goldberger/Lipsitz model for robustness where healthier (younger) and more robust systems exhibit more complexity in their physiological output and system complexity decrease with age. The mean whole brain fApEn demonstrated significant negative correlation ( r  = −0.472, p <0.001) with age. In comparison, SampEn produced a non-significant negative correlation ( r  = −0.099, p  = 0.367). fApEn also demonstrated a significant ( p  < 0.05) negative correlation with age regionally (frontal, parietal, limbic, temporal and cerebellum parietal lobes). There was no significant correlation regionally between the SampEn maps and age. These results support the Goldberger/Lipsitz model for robustness and have shown that fApEn is potentially a sensitive new method for the complexity analysis of fMRI data.